A study on the particle emission from cobalt-free studded tires against road materials - Olofsson, Ulf; Holmström, Erik; Lyu, Yezhe (Tribology international, 2025)
The use of studded tires can cause significant wear of road surfaces then also affect the air quality in urban areas. The studs of today’s studded tires are manufactured from hard metal containing cobalt. In this study, we investigated using alternative cobalt-free hard metal studs to reduce particulate emissions in the future. The tire-to-road interface is subjected to both impact wear and sliding abrasive wear. The alternative hard metal studs were evaluated in parallel with standard studs using two different laboratory test rigs specially designed for wear and particulate emission testing. Stone materials commonly used in the road tarmacadam were utilized as counter material. The results showed that the cobalt-free studs generated lower particle concentrations and less road wear. [Display omitted] •Two stud materials were evaluated in two dedicated test rigs for road wear and airborne particle emission studies.•One of the stud materials was a cobalt containing stud and the other one was a cobalt free alternative.•Lower particle emissions and road wear for the cobalt free stud compared to today’s standard cobalt containing one.